Expansão do Agronegócio e os Impactos Socioambientais na Região de Cerrados do Centro-Norte do Brasil (MATOPIBA) - Vicente Eudes Lemos Alves (Confins)
We propose with this study to understand these socio-environmental problems which are the results from the advancements of the monocultures agro-forests in the Biome of Savanna (“Cerrados”) of the Central North region of Brazil. We intend specially to understand the forms of impacts that the communities of agroextractivists have been suffering with the installation of agro-businesses in the region. The Central North region of Brazil in the area of the Biome Savanna corresponds to rich natural domains that shelters various regional ecosystems of which peasants populates and utilizes those areas intensively for the development of associated activities such as plant extractivisim, fishing and for small scale farming, designated, mostly for self consumption and for regional trade. The natural areas, several usages and the way the population uses them and their residence in those domains suffer threats due to the growth of forms of production bonded to agro-businesses of large scale, especially the advances of the monocultures of soy. The presence of that new economy which removes the original vegetation, that consumes elevated volumes of agro chemicals and that uses many natural resources has been generating various types of socio-environmental conflicts. From what was proposed, we intend to analyze the types of impacts that emerges from new productive context dominated from modern farming, especially those that were inserted on the environment and the regional population of agro extractivism.